Analysis of the driving factors of PM2.5 concentration in the air: A case study of the Yangtze River Delta, China. (March 2020) - Xu, Guoyu; Ren, Xiaodong; Xiong, Kangning; Li, Luqi; Bi, Xuecheng; Wu, Qinglin
Highlights: The factors affecting the PM2.5 concentration are different in different scales. Socioeconomic factors affect PM2.5 concentration in 30–50 km buffer significantly. The physical properties of the underlying surface affect the PM2.5 concentration. The WS, PF, PLC, P, NLI and PD affect the PM2.5 concentration mostly. Abstract: PM2.5 (particles <2.5 μm in aerodynamic diameter) has become the primary pollutant in the air of most cities in China, and it is an important index reflecting the degree of air pollution. In this study, the response of the PM2.5 concentration in the air to multiple factors reflecting the meteorological, underlying surface and socioeconomic conditions in the Yangtze River Delta region from 2001 to 2010 was investigated by Spearman correlation analysis, multivariate analysis of variance (MANOVA) and lasso regression. In consideration of the characteristics of natural conditions and intensity of human activities in the Yangtze River Delta region, we designed six spatial scales to explore finely the effects of each factor on PM2.5 concentration. The results may provide decision support for the cross-regional air pollution risk identification. The main conclusions are as follows: (1) In different buffer zones, the dominant factors affecting the PM2.5 concentration are different. The buffer zones of 30, 40 and 50 km are the most effective areas for socioeconomic factors to affect the PM2.5 concentration. (2) The physical properties of underlying surfaces have significant effects on the PM2.5 concentration. Forestland can reduce PM2.5 concentrations in air to a certain extent, while land for construction has the opposite effect. (3) The influence of natural factors on the PM2.5 concentration in air is greater than that of socioeconomic factors in the Yangtze River Delta region, but the influence of socioeconomic factors on the PM2.5 concentration in buffer zones of 30, 40 and 50 km can not be ignored. The WS (the wind speed), PF (the proportion of forestland), PLC (the proportion of land for construction), P (the precipitation), NLI (the night light index), and PD (the population density) are the six main factors affecting the PM2.5 concentration in air.